2019
DOI: 10.1140/epjc/s10052-019-6673-z
|View full text |Cite
|
Sign up to set email alerts
|

3D reconstruction of particle tracks in a 2 mm thick CdTe hybrid pixel detector

Abstract: We demonstrate how the latest generation of hybrid pixel detectors of the Timepix family can be used to reconstruct 3 dimensional particle tracks on a microscopic scale, additionally determining the stopping power along the particles' paths. In an experiment, a Timepix3 detector with a 2 mm thick planar CdTe sensor was irradiated in a 40 GeV/c pion beam and used in a similar way to a time-projection chamber: The coordinates x and y were given by the trajectory projection (pixel pitch: 55 µm), the z-coordinate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…The ToA is measured with a precision of 1.56 ns. The necessary energy calibration and time-walk correction methodology is described in [6] and [1,2], respectively.…”
Section: Detector Technology and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The ToA is measured with a precision of 1.56 ns. The necessary energy calibration and time-walk correction methodology is described in [6] and [1,2], respectively.…”
Section: Detector Technology and Methodologymentioning
confidence: 99%
“…Timepix3 as a solid-state time-projection chamber in particle and nuclear physics voltage. Using the known relation of the drift velocity as a function of the electric field, the drift time dependence on interaction depth can be determined analytically for silicon [2] or numerically for CdTe sensors [1]. It was found that a -resolution of~30 m and~60 m can be achieved in 500 m thick silicon and 2 mm thick CdTe sensors, respectively.…”
Section: Pos(ichep2020)720mentioning
confidence: 99%
See 2 more Smart Citations
“…Each pixel of the innovative TimePix chip comprises a preamplifier, a discriminator with threshold adjustment, synchronisation logic and a 14-bit counter. The operation of TimePix in time-over-threshold mode allows a 3D mapping of the charge spreading effect in the whole volume of the silicon sensor, thus differentiating between different types of particles species from mixed radiation fields and measuring their energy deposition [10].…”
Section: Timepix Radiation Monitorsmentioning
confidence: 99%